Molecular docking analysis between anti-apoptosis EGFR and four coumarins, and four carbazole alkaloids: in silico study - Afriza, Dhona; Suriyah, Wastuti Hidayati; Ichwan, Solachuddin Jauhari Arief; Knights, Joe (Universitas Padjadjaran, 2024)
Introduction: The anti-apoptotic protein EGFR is typically overexpressed in the majority of head and neck squamous cell carcinomas (HNSCC) and has been targeted for genetic therapy. The Clausena excavata plant is an evergreen shrub that has been widely used for various disease therapies, including cancer. Coumarin and carbazole alkaloids are the plant's primary active ingredients. This study aims to determine the molecular interaction between EGFR and several coumarins (clauslactone E, dentatin, nordentatin, clausenidin) and carbazole alkaloids (7- hydroxyheptaphylline, clausine E, 2,7 - dimethoxy - 9H - carbazole - 3- carbaldehyde,and 2,7 – dimethoxy - 9H - carbazole – 3-carboxylic acid). Methods: This research was carried out in silico using the molecular docking method. Molecular docking analysis was performed using AutoDock Vina, AutoDockTools 1.5.6., Pymol, and Discovery Studio Biovia 2021. The three-dimensional structure of the EGFR protein was retrieved from the RCSB Protein Data Bank. Ligands were obtained from the PubChem Compound Database. The comparison ligand was doxorubicin. Molecular docking results were analyzed based on binding affinity, amino acid interactions, visualization of docking results, and Lipinski's rule of five. Results: All of the investigated ligands with the EGFR receptor had strong binding affinity (-6.8 and -8.3 kcal/mol), almost the same as the comparison ligand (-8.2 kcal/mol). Each interaction also produced a different number of amino acid residues. Conclusion: These four coumarin compounds and four carbazole alkaloid compounds are considered potential EGFR inhibitors and anticancer candidates.KeywordMolecular docking, anticancer, oncogene protein, natural compunds